Hepatobiliary scintigraphy and liver function changes in patients with hepatocellular carcinoma treated with 166Ho-radioembolization - Margot T.M. Reinders; Maarten J.L. Smits; Karel van Erpecum; Joep de Bruijne; Rutger C.G. Bruijnen; Dave Sprengers; Rob de Man; Erik Vegt; Jan N.M. IJzermans; Marnix G.E.H. Lam; Arthur J.A.T. Braat (EJNMMI Research)
Abstract Background To study the feasibility of hepatobiliary scintigraphy (HBS) to improve selection and planning of patients with hepatocellular carcinoma (HCC) treated with holmium-166 (166Ho)-microspheres radioembolization. Results Thirty-one patients with HCC were included and treated with 166Ho- radioembolization as part of a prospective phase 2 study. Twenty-seven patients were eligible for analysis, 67% had a cirrhotic liver morphology on imaging, 70% had multifocal disease and 51% had bilobar disease. None of the patients had clinical signs of liver decompensation (Child Pugh ≤ B7, median MELD 9 or ALBI − 2.55). Global and regional hepatic function was based on manual delineation of HBS using 200 MBq 99mTc-mebrofenine, acquired during screening and approximately three months after 166Ho-radioembolization, referred to as liver clearance rate (LCR). In line with LCR at baseline, a significant correlation was found between LCR and lab results, including bilirubin, albumin, ALT, MELD-score, and ALBI-score (p < 0.05) during follow-up. HBS showed a significant decrease in median LCR (-16%; p = 0.0017) and volume (-17%; p = 0.0027) in the treated liver, without a significant increase in the non-treated liver. Median relative change in overall LCR in non-cirrhotics was 0% (range − 23–33%), in cirrhotics − 10% (range − 40 − 19%; p = 0.40). Conclusion HBS showed that hepatic function and volume significantly decreased in parts of the liver treated with 166Ho-microspheres radioembolization in patients with HCC. Cirrhotic patients do not seem to have the capacity to increase hepatic function in the treated part of the liver. Trial registration Registry name: Clinicaltrials.gov. Trial number: NCT03379844. Date of registration: 21 November 2017. Trial URL: https://clinicaltrials.gov/study/NCT03379844?cond=hcc&term=hepar primary&rank=1#study-overview .